Genetic variation in the Vitamin D related pathway and breast cancer risk in women of African ancestry in the Root Consortium - Wang, Shengfeng (Int J Cancer, 2017)
The vitamin D related pathway has been evaluated in carcinogenesis but its genetic contribution remains poorly understood. We examined single-nucleotide polymorphisms (SNPs) in the vitamin D related pathway genes using data from a genome-wide association study (GWAS) of breast cancer in the African Diaspora that included 3,686 participants (1,657 cases). Pathway- and gene-level analyses were conducted using the adaptive rank truncated product test. Odds ratios (OR) and 95% confidence intervals (CI) were estimated at SNP-level. After stringent Bonferroni corrections, we observed no significant association between variants in the vitamin D pathway and breast cancer risk at the pathway-, gene-, or SNP-level. In addition, no association was found for either the reported signals from GWASs of vitamin D related traits, or the SNPs within vitamin D receptor (VDR) binding regions. Furthermore, a decrease in genetically predicted 25(OH)D levels by Mendelian randomization was not associated with breast cancer (P = 0.23). However, an association for breast cancer with the pigment synthesis/metabolism pathway almost approached significance (pathway-level P = 0.08), driven primarily by a nonsense SNP rs41302073 in TYRP1, with an OR of 1.54 (95% CI = 1.24–1.91, P(adj) = 0.007). In conclusion, we found no evidence to support an association between vitamin D status and breast cancer risk in women of African ancestry, suggesting that vitamin D is unlikely to have significant effect on breast carcinogenesis. Interestingly, TYRP1 might be related to breast cancer through a non-vitamin D relevant mechanism but further studies are needed.